Exploring Local Linguistic Scenery Amongst Superdiversity A Small Place in the Global Landscape. - Atanassova, Svetlana (Cambridge Scholars Publishing, 2022)
This book provides a linguistic snapshot of a small urban place, the town of Veliko Turnovo in Bulgaria. It investigates public signs and the inscriptions on them from the perspective of linguistic landscaping studies (LLS), a branch of sociolinguistics. Its study of the local linguistic landscape is carried out in the context of globalization and cultural and linguistic super-diversity. The book focuses on the presence of foreign languages in the Bulgarian public space with a particular emphasis on the use of English as Globe Talk. It also explores the different kinds of literacy, which peopl.